Photobiomodulation in the treatment of oral diseases (Research, Society and Development, 2023)
The modern conception of dentistry is based on the search for noninvasive clinical applicability methods that improve the prognoses of dental pathologies and, therefore, the interest in light-tissue interaction technology has increased in the last decade. The present study aims to explore the applicability of photobiomodulation (PBM) in dentistry with emphasis on wavelengths provided to target tissues and the underlying mechanisms of action of lasers observed in the treatment of various oral diseases, as well as the affected processes that include, but are not limited to wound healing, tissue biostimulation, tissue and nerve regeneration, inhibition of pain and inflammatory processes. The effects obtained through photobiomodulation are correlated with the parameters involved, such as the equipment used, wavelength, power dosages, irradiation duration, energy density, general patient conditions, target tissue, pathology and etiologies considered. Depending on the conditions reported, the photobiomodulator effect or also known as low intensity laser therapy (LLLT) influences the increase of cellular metabolism through the application of photonic energy that presents monochromaticity and propagates consistently in time and space. Thus, the protocols for the application of the photonic properties of this therapeutic modality should be analyzed in the treatment of oral conditions and pathologies associated with glandular, neural, autoimmune, traumatic, and idiopathic diseases.